An iron wind : Europe under Hitler - Fritzsche, Peter, 1959- (Basic Books, 2016)
"Unlike World War I, when the horrors of battle were largely confined to the front, World War II reached into the lives of ordinary people in an unprecedented way. Entire countries were occupied, millions were mobilized for the war effort, and in the end, the vast majority of the war's dead were non-combatant men, women, and children. Inhabitants of German-occupied Europe--the war's deadliest killing ground--experienced forced labor, deportation, mass executions, and genocide. As direct targets of and witnesses to violence, rather than far-off bystanders, civilians were forced to face the war head on. Drawing on a wealth of diaries, letters, fiction, and other first-person accounts, award-winning historian Peter Fritzsche redefines our understanding of the civilian experience of war across the vast territory occupied and threatened by Nazi Germany. Amid accumulating horrors, ordinary people across Europe grappled with questions of faith and meaning, often reaching troubling conclusions. World War II exceeded the human capacity for understanding, and those men and women who lived through it suspected that language could not adequately register the horrors they saw and experienced. But it nevertheless prompted an outpouring of writing, as people labored to comprehend and piece thoughts into philosophy. Their broken words are all we have to reconstruct how contemporaries saw the war around them, how they failed to see its terrible violence in full, and how they attempted to translate the destruction into narratives. Carefully reading these testimonies as no historian has done before, Fritzsche's groundbreaking work sheds new light on the most violent conflict in human history, when war made words inadequate, and the inadequacy of words heightened the devastation of war"--